2014
DOI: 10.1002/hec.3063
|View full text |Cite
|
Sign up to set email alerts
|

Intended and Unintended Consequences of Minimum Staffing Standards for Nursing Homes

Abstract: Staffing is the dominant input in the production of nursing home services. Because of concerns about understaffing in many US nursing homes, a number of states have adopted minimum staffing standards. Focusing on policy changes in California and Ohio, this paper examined the effects of minimum nursing hours per resident day regulations on nursing home staffing levels and care quality. Panel data analyses of facility-level nursing inputs and quality revealed that minimum staffing standards increased total nursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 53 publications
0
79
0
Order By: Relevance
“…There are also reasons to suspect that workers in the public and private sectors may respond very differently to reduced capacity. 5 Chen and Grabowski (2015), Bowblis (2011), Park and Stearns (2009) for problems including omitted variable bias and endogeneity of staffing levels (Evans and Kim, 2006). 4 Second, most prior work on exogenous capacity changes in health care settings focuses on increased rather than reduced capacity.…”
Section: Introductionmentioning
confidence: 99%
“…There are also reasons to suspect that workers in the public and private sectors may respond very differently to reduced capacity. 5 Chen and Grabowski (2015), Bowblis (2011), Park and Stearns (2009) for problems including omitted variable bias and endogeneity of staffing levels (Evans and Kim, 2006). 4 Second, most prior work on exogenous capacity changes in health care settings focuses on increased rather than reduced capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Munnich (2014) used a different model and set of comparison states and came to a different conclusion. Chen and Grabowski (2015) emphasize that a full understanding of the implications of minimum staffing regulations must encompass intended and unintended consequences. Using the American Community Survey (ACS) and Current Population Survey (CPS) data from 2001 to 2007, Munnich concluded that the number of RNs working at hospitals in California did not grow at a faster rate than in the 15 comparison states.…”
Section: Introductionmentioning
confidence: 99%
“…Applying a DD model for independent cross-sections, Munnich found mixed evidence on RN wages-a 4.4% increase using the ACS but a statistically insignificant 3.8% decrease using the CPS-and attributed the anomalous combination of higher staffing and modest or no effects on wages to the closure of 15 California hospitals from 2003 to 2005 and the reclassification or reassignment of RNs from managerial duties to patient care. Chen and Grabowski (2015) emphasize that a full understanding of the implications of minimum staffing regulations must encompass intended and unintended consequences. An increase in RN wages is one such potential unintended consequence, and the existence of such a change would magnify the effect of staffing regulations on operating expenses and margins and uncompensated care provided (Reiter, Harless, Pink, & Mark, 2012;Reiter, Harless, Pink, Spetz, & Mark, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…An exception in this regard is staff-to-patient ratios about which there is fairly compelling evidence from the US context. Studies have shown higher staffing levels to be positively associated with high quality care in nursing homes (at least when measured using clinically-oriented outcome indicators) (Spilsbury et al 2011), fewer severe deficiency citations and an improvement in certain health conditions requiring intensive nursing care (Chen and Grabowski 2014). As a result of this lack of evidence and a concern to better reflect system goals, some countries have developed standards that focus on aspects of process or outcome quality.…”
Section: Ltc Servicesmentioning
confidence: 99%
“…(Although this may not have negative consequences for the quality of care, see e.g. Chen and Grabowski 2014). Ikegami et al (2014) suggest that the reason nursing agencies in Japan have not expanded as fast as home helper agencies is because nurses are three times as expensive as care workers.…”
Section: Assessment Of the Regulatory Context For Ltc Professionals Amentioning
confidence: 99%